2017
DOI: 10.1002/pi.5362
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of multiwall carbon nanotube/waterborne polyurethane nanocomposites

Abstract: The preparation of thermoplastic nanocomposites of waterborne polyurethane (WBPU) and multiwall carbon nanotubes (MWCNTs) via an in situ polymerization approach is presented. The effects of the presence and content of MWCNTs on the morphology and thermal, mechanical and electrical properties of the nanocomposites were investigated. Carbon nanotubes were modified with amide groups in order to enhance their chemical affinity towards WBPU. Thermogravimetric studies show enhanced thermal stability of the nanocompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…As shown in Figure 13A, the cross‐sectional image of the pure polyurethane film is smooth and flat. Figure 13B,C, corresponding to composites with 0.1 and 0.2 wt% of acid‐MWCNTs, respectively, showed well‐dispersed due to formation of hydrogen bonds between acid‐MWCNTs and polymer matrix 31 . As a result, the preparing WPU/acid‐MWCNTs nanocomposites with the low content of acid‐MWCNTs had a better performance in terms of mechanical properties and thermal stability.…”
Section: Resultsmentioning
confidence: 95%
“…As shown in Figure 13A, the cross‐sectional image of the pure polyurethane film is smooth and flat. Figure 13B,C, corresponding to composites with 0.1 and 0.2 wt% of acid‐MWCNTs, respectively, showed well‐dispersed due to formation of hydrogen bonds between acid‐MWCNTs and polymer matrix 31 . As a result, the preparing WPU/acid‐MWCNTs nanocomposites with the low content of acid‐MWCNTs had a better performance in terms of mechanical properties and thermal stability.…”
Section: Resultsmentioning
confidence: 95%
“…A broad peak at 3,481 cm −1 corresponds to the hydrogen‐bonding NH stretching with urethane carbonyl groups and a peak at 1,539 cm −1 corresponds to CN stretching and δNH stretching. The peaks at 2,970 and 2,848 cm −1 are attributed to the stretching of CH bond in CH 3 and CH 2 groups, respectively . The stretching peaks at 1,716 and 1,645 cm −1 correspond to the urea hydrogen bonded disordered carbonyl group and urethane hydrogen bonded disordered carbonyl group, respectively.…”
Section: Resultsmentioning
confidence: 98%
“…Inorganic nanoparticles, such as SiO 2 , TiO 2 , ZnO , and clay nanocomposites are widely used to improve thermal stability, mechanical and physical properties of waterborne polyurethanes. Macromolecular organic nanomaterials, such as N ‐doped reduced graphene oxide (NRGO) , carbon canotube , and high aspect ratio nanofibrillated cellulose , are used to endow the WPU with quality electromagnetic interference shielding effectiveness (EMI SE), mechanical properties, thermal properties and water resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Figure (c,f,i) suggests that the Young's modulus of WPUA film increased from 19.1 to 25.4 MPa after GO addition, and it increased to 30.6 MPa after PG addition; this suggests improvements in the mechanical strength of the film after the modifier addition. The excellent dispersion of GO and PG enhanced the uniformity of stress distribution and reduced the stress concentration, thereby improving the mechanical properties. Furthermore, the Young's modulus of PG–WPUA was higher than those of previously reported waterborne PU–multiwall carbon nanotubes (7.2 MPa) and PU nanocomposites filled with attapulgite nanorods (9.12 MPa); this suggested that the superior nature of the PG–WPUA films showed great promise for practical applications.…”
Section: Resultsmentioning
confidence: 99%